3/7p=6

Simple and best practice solution for 3/7p=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3/7p=6 equation:


p in (-oo:+oo)

(3/7)*p = 6 // - 6

(3/7)*p-6 = 0

3/7*p-6 = 0 // + 6

3/7*p = 6 // : 3/7

p = 6/3/7

p = 14

p = 14

See similar equations:

| 4(x-2)(x+2)=4x^2-12x+6 | | 57x+136=90 | | 57x+136=180 | | 2-r=-4 | | f(5x)=(2x^2)-7 | | X^2-6x-5=x | | 57x+136= | | -(-6y+7z-8x)= | | 5log(3x+5)=12 | | 7x-3x+2=-8x-i | | -(6y+7z-8x)= | | (10-t)(10+t)=0 | | 6x+2(5x+12)=25-2(1-8x) | | 16-2t=3/2t | | X+.20x+35=89 | | 25.20x+20=71 | | 2n+6n=72 | | 25.20x+0.20=71 | | 7x-21=7(x-4)+7 | | 42x=-64 | | a^2b-b^3= | | (9k-2)2=0 | | 17x-7=0 | | (21y-1)+(4x+23)+(9x-38)=180 | | 2y^3/4h^2(2y^1/3h^-4)^6 | | 4x-10=x-1 | | -(3z+2x)= | | 85-3=49 | | a^2-12a+26=-6 | | -7=13+.4b | | (10-t)(10+r)=0 | | 8/3c-2=2/3c=12 |

Equations solver categories